The effect of polyphenol-rich dark chocolate on fasting capillary whole blood glucose, total cholesterol, blood pressure and glucocorticoids in healthy overweight and obese subjects - Almoosawi, Suzana; Fyfe, Lorna; Ho, Clement; Al-Dujaili, Emad (British journal of nutrition, 2010)
Numerous studies indicate that polyphenol-rich chocolate reduces fasting blood glucose, blood pressure (BP) and total cholesterol in healthy individuals and hypertensives with or without glucose intolerance. The aim of the present study was to investigate the effect of two doses of polyphenol-rich dark chocolate (DC) on fasting capillary whole blood glucose, total cholesterol and BP and to examine whether improvements in these parameters are associated with changes in adrenocorticoid excretion in overweight and obese individuals. The study used a randomised, single-blind, cross-over design where fourteen overweight and obese subjects were randomised to either take 20 g DC with 500 mg polyphenols then 20 g DC with 1000 mg polyphenols or vice-versa. Participants followed each diet for 2 weeks separated by a 1-week washout period. It was observed that the 500 mg polyphenol dose was equally effective in reducing fasting blood glucose levels, systolic BP (SBP) and diastolic BP (DBP) as the 1000 mg polyphenol dose suggesting that a saturation effect might occur with increasing dose of polyphenols. There was also a trend towards a reduction in urinary free cortisone levels with both groups although it did not reach statistical significance. No changes in anthropometrical measurements were seen. We suggest that more research is required to investigate the mechanism(s) by which polyphenol-rich foods influence health.